EFEKTIVITAS LAYANAN BIMBINGAN KLASIKAL TEKNIK LIVE MODELING UNTUK MENINGKATKAN KEMAMPUAN PERENCANAAN KARIER PESERTA DIDIK SMP TINGKAT VIII - Zulfiona Fitra Al Faroza; Rima Irmayanti; Risma Amelia (IKIP Siliwangi, 2026)
Everything will function more smoothly and successfully with the aid of career planning, which enables people to recognize and formulate actionable actions toward achieving their professional objectives. The purpose of this study was to determine how the traditional guidance services combined live modeling methods on career planning for eighth-grade students at SMPN 5 Cimahi The study employed quantitative research approaches and had sample 76 students in total, with 38 students in each session. The experimental and control groups were established use a quasi-experimental non-equivalent control group design technique. A career planning survey tool was employed, and a portion of the information was derived from the 1958 theory of John Milton Dillard. The researcher was assigned to the effective group after achieving an average n-gain test score of 90.7% in the experimental class. By contrast, the average n-gain test result for the control class was 54.1%, putting it in the less effective group. Students in the eighth grade at SMPN 5 Cimahi believe that career preparation is greatly benefited by traditional mentoring via direct modeling approaches.